The effectiveness of family welfare movement program in slums - Asih Kuswardinah (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
Demands for family needs are increasing along with the changing times and science. Thus, Family Welfare Program or Program Kesejahteraan Keluarga (PKK) is nationally aimed to empower families to improve prosperity towards faith and devotion to God; virtuous morality; health; prosperity; independence; gender equality, justice; legal and environmental awareness. This paper aims to provide a descriptive picture to PKK Deliksari management about the level of implementation of the members of each workgroup program (I, II, III, IV); give a picture to PKK management about which workgroup is responded mostly by members; provide an overview of the skills education that is most interesting in Deliksari community, so it can be followed up through village entrepreneurship training; provide an overview of facilities needed to motivate the community to increase efforts. The research was conducted in Deliksari. The total respondents are 58 people determined by purposive sampling. The data collection tool is questions with multiple answers corroborated by in-depth interviews with management, some members, and field observations. The study found that the achievement of program implementation percentage included the average achievement of workgroup I in the high category; the average achievement of workgroup II in the medium category; the average achievement of workgroup III in the medium category, the average achievement of workgroup IV in the medium category; the average achievement of workgroup I to IV in the medium category; and the highest percentage, that is, from residents choosing